Arachnoid Cyst with a Non-traumatic Acute Subdural Hematoma in an Eleven-year-old Patient - Cavasana, Gabriel Flamarin; Mendonça, Rodrigo; Zanini, Fabricio Willian Mantelo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
A non-traumatic intra-cystic hemorrhage in an arachnoid cyst is a rare event, with few cases reported in the literature. We present a case of an eleven-year-old boy patient, which presented a spontaneous acute subdural hematoma and intra-cystic hemorrhage after a strong headache episode. The results were evidenced by a computed tomography (CT) scan and surgical findings. We perform a brief literature review on the arachnoid cyst and its suggested treatments. In our case, the patient underwent a surgical treatment with a complete resolution of the case.
Keywords: neurosurgery; arachnoid cysts; acute subdural hematoma